The Effect of Solvency, Profitability, Liquidity, and Sales Growth Ratio on Financial Distress (Case Study of a Transportation Company Listed on the Indonesian Stock Exchange) - Aprilani, Lutfi Alfiana; Haningsih, Luna (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This study aims to analyse the effect of financial ratios on Financial Distress, namely the effect of debt to asset ratio (DAR), return on equity (ROE), current ratio (CR), and sales growth. The population in this study are transportation companies listed on the Indonesia Stock Exchange in 2018-2022. The samples used were 15 companies with indications of Financial Distress from the calculation of negative earnings per share. The sampling method in this study used purposive sampling. The data collection method uses the library method, by taking financial reports on the IDX.co.id website or the official website of a transportation company listed on the Indonesia Stock Exchange. Methods of data analysis using descriptive and panel data regression. The results showed that the variable (1) debt to asset ratio (DAR) has negative and significant influence on financial distress of transportation companies, (2) current ratio (CR) and (3) sales growth has positive and significant significant influence on financial distress of transportation companies, and (4) return on equity (ROE) do not influence on financial distress of transportation companies listing on Indonesia Stock Exchange period 2018-2022.